Strategi Partai Gerindra dalam Memenangkan Dahlan Hasan dan Muhammad Ja’far Sukhairi Nasution Sebagai Bupati dan Wakil Bupati Mandailing Natal - Muhammad Sukri; Rudi Salam Sinaga; Aswin Hasibuan (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2020)
Pilkada is a means to realize the sovereignty of the people in government, therefore Pilkada must be held in a quality manner with the broadest participation of the people. The purpose of the study was to find out how the Gerindra Party's strategy in winning Dahlan Hasan Nasution Ja'far Sukhairi Nasution as the Regent and Deputy Regent of Mandailing Natal District as well as the obstacles experienced during the campaign. The type of research used in this study is a qualitative research method. And the theory used in this research is Henry Mintzberg's theory, James Brian which includes, strategies as plan, ploy, pattern, position, perspective. Approaching community leaders, academics, village heads, mass organizations and visiting every time there is a crowd in the community are the main points that are carried out. with the systemic campaign, the community is convinced that the couple is a worthy partner to be chosen to be the leader in their area so that the pair is able to obtain 56.67% of the votes.